ARTIFICIAL INTELLIGENCE AND FREE WILL: A BUDDHIST ETHICAL PERSPECTIVE - Lauw, Acep; Kwang, Jeni (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2025)
The development of artificial intelligence (AI) presents significant ethical challenges, particularly concerning free will and moral responsibility. This research examines the morality of AI technology from a Buddhist perspective, emphasizing key concepts such as karma, cetana (intention), paticcasamuppada (dependent origination), mindfulness, compassion (karuna), and the principle of non-harm (ahimsa). The methodology employed in this study is a literature review with a qualitative approach based on thematic content analysis. The findings indicate that AI has the potential to support human well-being when designed with good intentions and heightened awareness; however, it also risks diminishing individual autonomy if used without deep ethical reflection. This study offers an ethical framework based on Buddhist teachings that underscores the importance of transparency, responsibility, and moral balance in technology development. These findings contribute to the discourse on AI ethics by enriching the dominant Western framework through a holistic approach derived from Eastern traditions.